The treasures of William Shakespear - Alexander, Catherine M.S. (London, United Kingdom : Andre Deutsch, 2014)
William Shakespeare is the best-known dramatist in the world and his plays, plots. characters and language have outlived their original context of the Elizabeth and Jacobean playhouse.
Introduction -- The Elizabethan Age- the court -- The Elizabethan Age-the country -- Elizabethan Stratford -- Shakespeare in Stratford -- Shakespeare's London -- Shakespeare's Contemporaries -- The Elizabethan Stage -- Shakespeare's Texts -- " The Plays the Thing" -- The Comedies- happily ever after -- The Comedies- distorting the convention -- The History Plays- the first tetralogy -- The History Plays-the second tetralogy ...
Keywords: HISTORY